2016
DOI: 10.1128/jvi.02843-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of N Terminus-Truncated NS1 Proteins of Influenza A Virus in Inhibiting IRF3 Activation

Abstract: The NS1 protein encoded by influenza A virus antagonizes the interferon response through various mechanisms, including blocking cellular mRNA maturation by binding the cellular CPSF30 3= end processing factor and/or suppressing the activation of interferon regulatory factor 3 (IRF3). In the present study, we identified two truncated NS1 proteins that are translated from internal AUGs at positions 235 and 241 of the NS1 open reading frame. We analyzed the cellular localization and function of the N-truncated NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…As new variant proteins are identified by the influenza research community and reported in the scientific literature (26), the IRD team evaluates the strength of evidence for the presence and importance of these novel proteins, determines the sequence signals that can be used to predict their expression, and adds the specific prediction algorithm to our variant protein prediction infrastructure, making these sequence annotations uniquely available in IRD for user query and downstream analysis.…”
Section: Future Developmentsmentioning
confidence: 99%
“…As new variant proteins are identified by the influenza research community and reported in the scientific literature (26), the IRD team evaluates the strength of evidence for the presence and importance of these novel proteins, determines the sequence signals that can be used to predict their expression, and adds the specific prediction algorithm to our variant protein prediction infrastructure, making these sequence annotations uniquely available in IRD for user query and downstream analysis.…”
Section: Future Developmentsmentioning
confidence: 99%
“…One function of the NS1 protein is to bind the TRIM25 E3 ligase, inhibiting its multimerization and thus its ligase activity, an action that was postulated to block activation of the RIG-I pathway (Gack et al, 2009). However, not all human-circulating influenza A virus strains block RIG-I-mediated activation of IRF3 and interferon-β transcription (Kuo et al, 2016; 2010), although the NS1 proteins of all tested strains bind TRIM25 (Gack et al, 2009; Kuo et al, 2010; Rajsbaum et al, 2012). Notably, strong activation of IRF3 and interferon-β transcription still occurs in cells infected with viruses expressing NS1 proteins of human-circulating H3N2 and H2N2 viruses (Kuo et al, 2010; 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all human-circulating influenza A virus strains block RIG-I-mediated activation of IRF3 and interferon-β transcription (Kuo et al, 2016; 2010), although the NS1 proteins of all tested strains bind TRIM25 (Gack et al, 2009; Kuo et al, 2010; Rajsbaum et al, 2012). Notably, strong activation of IRF3 and interferon-β transcription still occurs in cells infected with viruses expressing NS1 proteins of human-circulating H3N2 and H2N2 viruses (Kuo et al, 2010; 2016). Consequently, binding of TRIM25 by the NS1 protein does not directly correlate to the suppression of interferon-β induction in influenza A virus-infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…The data are presented as the means ± SD derived from three repeat experiments. *P < 0.05 or **P < 0.01, ***P < 0.001 (Student's t-test).Qian et al NS1 Inhibits IFN-β through TRAF3 Frontiers in Immunology | www.frontiersin.org July 2017 | Volume 8 | Article 779translated from internal AUGs at positions 235 and 241 of the NS1 open reading frame, were found to inhibit the activation of IRF3 and IFN-β transcription(41). This observation is supported by our findings that the influenza A virus NS1 ED plays an important role in the ability of the NS1 protein to inhibit IFN-β pathway.…”
mentioning
confidence: 99%